2013
DOI: 10.1093/nar/gkt751
|View full text |Cite
|
Sign up to set email alerts
|

The mycobacterial antibiotic resistance determinant WhiB7 acts as a transcriptional activator by binding the primary sigma factor SigA (RpoV)

Abstract: Tuberculosis therapeutic options are limited by the high intrinsic antibiotic resistance of Mycobacterium tuberculosis. The putative transcriptional regulator WhiB7 is crucial for the activation of systems that provide resistance to diverse antibiotic classes. Here, we used in vitro run-off, two-hybrid assays, as well as mutagenic, complementation and protein pull-down experiments, to characterize WhiB7 as an auto-regulatory, redox-sensitive transcriptional activator in Mycobacterium smegmatis. We provide the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
119
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 62 publications
5
119
0
Order By: Relevance
“…In Mycobacterium tuberculosis, WhiB3 acts as a metabolic regulator that binds to the promoters of polyketide biosynthetic genes (13), while WhiB6 acts as an initial phagosomal signal receptor (14). It has also been shown that WhiB7 is a critical protein for generating resistance to antibiotics in M. tuberculosis (15). Recently, whiB3 (16), whiB4 (17), whiB5 (18), and whiB2 (19) were shown to play essential roles in the virulence of M. tuberculosis during progressive infection.…”
mentioning
confidence: 99%
“…In Mycobacterium tuberculosis, WhiB3 acts as a metabolic regulator that binds to the promoters of polyketide biosynthetic genes (13), while WhiB6 acts as an initial phagosomal signal receptor (14). It has also been shown that WhiB7 is a critical protein for generating resistance to antibiotics in M. tuberculosis (15). Recently, whiB3 (16), whiB4 (17), whiB5 (18), and whiB2 (19) were shown to play essential roles in the virulence of M. tuberculosis during progressive infection.…”
mentioning
confidence: 99%
“…Direct biochemical evidence (transcriptional run off experiments) has assigned transcriptional regulatory functions to WhiB proteins, including whiB1 (31,32), a repressor, and whiB7, an activator (33). In vitro transcriptional run-off studies have shown that the M. smegmatis WhiB7 protein is a redox-sensitive transcriptional activator of its own promoter (33).…”
mentioning
confidence: 99%
“…Direct biochemical evidence (transcriptional run off experiments) has assigned transcriptional regulatory functions to WhiB proteins, including whiB1 (31,32), a repressor, and whiB7, an activator (33). In vitro transcriptional run-off studies have shown that the M. smegmatis WhiB7 protein is a redox-sensitive transcriptional activator of its own promoter (33). The whiB7 promoter, conserved across mycobacteria and other Actinobacteria, includes an AT-rich motif directly upstream of its Ϫ35 hexamer that is targeted by WhiB7 to promote transcription (9,33).…”
mentioning
confidence: 99%
See 2 more Smart Citations